2021
DOI: 10.1111/ejh.13577
|View full text |Cite
|
Sign up to set email alerts
|

Myelomonocytic skewing in chronic myelomonocytic leukemia: phenotypic, molecular and biologic features and impact on survival

Abstract: Background Myelomonocytic skewing is considered as a key pathophysiologic phenomenon in chronic myelomonocytic leukemia (CMML), but its prevalence and potential correlation with phenotypic, genotypic, and clinical features are poorly defined. Methods Skewed differentiation toward the myelomonocytic over erythroid commitment as indicated by an inverse ratio of myelomonocytic/erythroid colonies was investigated in 146 patients with CMML by semisolid in vitro cultures. Results There was a high prevalence of myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Median values and ranges of CFU‐GM/10 5 MNC were 0.5 (0–3), 3 (0–35), and 59 (3–202), in T, TS, and TSN, respectively (Table ). Myelomonocytic skewing is another important in vitro characteristic in CMML and is indicated by a higher number of myeloid over erythroid colonies from PBMNC 14,15 . As we have reported previously, there was a high prevalence of myelomonocytic skewing in CMML patients (120/146, 82%), whereas this phenomenon was rare in normal individuals (1/98, 1%) 15 .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Median values and ranges of CFU‐GM/10 5 MNC were 0.5 (0–3), 3 (0–35), and 59 (3–202), in T, TS, and TSN, respectively (Table ). Myelomonocytic skewing is another important in vitro characteristic in CMML and is indicated by a higher number of myeloid over erythroid colonies from PBMNC 14,15 . As we have reported previously, there was a high prevalence of myelomonocytic skewing in CMML patients (120/146, 82%), whereas this phenomenon was rare in normal individuals (1/98, 1%) 15 .…”
Section: Resultssupporting
confidence: 59%
“…[10][11][12] The biologic basis for this observation was provided by Padron et al when he reported hypersensitivity of CMML progenitors using phospho-STAT5 flow cytometry. 26 Moreover, our group could show in a small retrospective study that CMML patients with high spontaneous CFU-GM growth (>100/10 15 In this study, we found that myelomonocytic skewing was not observed in the CMML patients with a TET2 mutation alone, but was seen in more than half of the patients who had only a TET2/SRSF2 mutation and in all patients who had additional NRAS mutations. This indicates that the preferential expansion of myelomonocytopoiesis over erythropoiesis in CMML is a biologic phenomenon starting at the CMML stage characterized by the comutation of genes of the epigenetic and the spliceosome regulation and further parallels the progression of CMML into more advanced disease.…”
Section: Discussionmentioning
confidence: 56%
“…Semisolid in vitro cultures from PBMNC of normal individuals usually contain a higher concentration of erythroid colonies (BFU-E) as compared to myeloid colonies (CFU-GM). Skewed differentiation toward the myelomonocytic over erythroid commitment in patients, as indicated by an inverse BFU-E/CFU-GM ratio, is a common finding in CMML patients ( 39 ). Interestingly, the lack of myelomonocytic skewing separated patients with a particularly favorable prognosis and a minimal risk of transformation.…”
Section: Pathogenesis Of Cmmlmentioning
confidence: 99%
“…Geissler et al. could demonstrate that myelomonocytic skewing as determined by semisolid cultures can separate subgroups of CMML patients with a different phenotype, a different genotype and a different prognosis ( 39 ). The definitive link of this phenomenon to the pathophysiology of CMML comes from animal studies in which hematopoietic cells are genetically manipulated with molecular aberrations that are commonly found in CMML patients.…”
Section: Pathogenesis Of Cmmlmentioning
confidence: 99%
See 1 more Smart Citation